2009
DOI: 10.1242/dmm.002113
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell-derived motor neurons expressing SOD1 mutants exhibit typical signs of motor neuron degeneration linked to ALS

Abstract: SUMMARY Human embryonic stem cell (hESC)-derived neurons have the potential to model neurodegenerative disorders. Here, we demonstrate the expression of a mutant gene, superoxide dismutase 1(SOD1), linked to familial amyotrophic lateral sclerosis (ALS) in hESC-derived motor neurons. Green fluorescent protein (GFP) expression under the control of the HB9 enhancer was used to identify SOD1-transfected motor neurons that express human wild-type SOD1 or one of three different mutants (G93A, A4V and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
1
44
1
Order By: Relevance
“…With the development of culture systems to efficiently generate neural lineage and functional neurons from human pluripotent stem cells, these systems have been used to model neurogenetic disorders through the manipulation of disease-determining genes in hESCs or the generation of patient-specific iPSCs [26,[40][41][42][43][44]. To be an ideal disease model, the culture system should be able to generate the target neurons efficiently and to recapitulate the in vivo pathological process in these target neurons.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of culture systems to efficiently generate neural lineage and functional neurons from human pluripotent stem cells, these systems have been used to model neurogenetic disorders through the manipulation of disease-determining genes in hESCs or the generation of patient-specific iPSCs [26,[40][41][42][43][44]. To be an ideal disease model, the culture system should be able to generate the target neurons efficiently and to recapitulate the in vivo pathological process in these target neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The cells organize into neural tube-like rosettes and, after 7-8 days in culture, sonic hedgehog (Shh) and cyclic adenosine monophosphate (cAMP) are added to the culture media for one additional week [34]. Alternatively, the human EBs can be held as suspension cultures in the absence of bFGF for 6 days, followed by cell plating on laminin-coated dishes in N2 medium [24,35]. After 6 days, RA is added and the cells differentiate for 3 days until columnar cells form [24,35].…”
Section: Neuroepithelial Cells Achievementmentioning
confidence: 99%
“…Alternatively, the human EBs can be held as suspension cultures in the absence of bFGF for 6 days, followed by cell plating on laminin-coated dishes in N2 medium [24,35]. After 6 days, RA is added and the cells differentiate for 3 days until columnar cells form [24,35]. Medium consisting of F12/DMEM, N2 supplement with heparin (2 g/ml), Shh, RA and cAMP with or without FGF2 can be used for 15 days [36,37].…”
Section: Neuroepithelial Cells Achievementmentioning
confidence: 99%
“…Human ESCs were also used to study the cell-autonomous mechanisms involved in motor neuron degeneration. In 2009 a human embryonic stem cell line was used to generate motor neurons that were then transfected with different constructs containing SOD1 mutations (35). In line with the study performed in SOD1 G93A mESC-derived motor neurons, the authors observed a reduction in neurite length and reduced cell survival.…”
Section: Human Escs and Ipscsmentioning
confidence: 86%